2001
DOI: 10.1067/mva.2001.117147
|View full text |Cite
|
Sign up to set email alerts
|

Expanded application of in situ replacement for prosthetic graft infection

Abstract: In situ replacement was a safe and durable option in most (64%) patients presenting with prosthetic graft infection. In situ replacement with a rifampin-bonded graft was effective for S epidermidis graft infection, but when the entire prosthesis is involved with either a biofilm or invasive perigraft infection, in situ autogenous vein replacement is preferred. Virulent graft infections presenting with sepsis, anastomotic dehiscence, or graft enteric fistula should continue to be treated with total graft excisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 19 publications
4
150
1
5
Order By: Relevance
“…Data from the initial report [113][114][115][116][117][118][119] of a national surveillance system created by the Centers for Disease Control and Prevention to monitor infection in outpatient hemodialysis patients demonstrate the proclivity for vascular access site infection. The overall vascular access site infection rate was 3.2 per 100 patient-months.…”
Section: Hemodialysis Prosthetic Vascular Graftsmentioning
confidence: 99%
“…Data from the initial report [113][114][115][116][117][118][119] of a national surveillance system created by the Centers for Disease Control and Prevention to monitor infection in outpatient hemodialysis patients demonstrate the proclivity for vascular access site infection. The overall vascular access site infection rate was 3.2 per 100 patient-months.…”
Section: Hemodialysis Prosthetic Vascular Graftsmentioning
confidence: 99%
“…Aortic resection with extraanatomic bypass carries a low risk of postsurgical infection but is associated with poor patency rates of the bypass graft despite anticoagulation and adverse outcomes including aortic stump disruption, bleeding, a higher rate of lower extremity amputation and compromised blood supply to the pelvis, colon and rectum (Oderich et al, 2011). Case reports have shown that in situ reconstruction with various types of grafts lead to good long-term results (Noel et al, 2002;Nevelsteen et al, 1995;Bandyk et al, 2001;Batt et al, 2003) but this has not been supported by randomized controlled trials. Weis- Muller et al (2011) described a 42% mortality with the use of grafts and dacron patches for in-situ reconstruction of mycotic aortic aneurysm infected with various other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Reported mortality rates range between 11-22%, while limb loss 10-11%. [20,29] Stump blowout, which is a major complication, can happen up to 22% of the cases. [7] Several authors suggest that staged management of infected aortic grafts, show lower morbidity and mortality rates.…”
Section: Graft Excisionmentioning
confidence: 99%
“…S. Epidermidis) and the anastomoses are spared. [20] For example in segmental aortofemoral graft infections, with groin complications, especially in elderly patients, antibiotic bonded prosthetic grafts should be considered for replacement of one limb of the pre-existing graft. An alternative option, especially in more diffuse infections, is the use of cryopreserved arterial allografts.…”
Section: Graft Excisionmentioning
confidence: 99%